ABOUT THE MANUSCRIPT FUND OF THE MUSEUM OF LITERATURE - Shafoat Khasanova (International Scientific and Current Research Conferences, 2022)
The article tells about the establishment of the Manuscript Fund of the Academy of Sciences of the Republic of Uzbekistan named after Alisher Navoi since its inception, as well as the successful work of Hamid Suleymanovich Suleymanov in the search and collection of monuments of our spiritual heritage.